CHILDFREE: BETWEEN HUMAN POPULATION ISSUES AND THE PURPOSE OF MARRIAGE IN ISLAM (MAQASID AL-NIKAH) - Moch. Nurcholis; Muhammad Rizki Maulana (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
In Islam the main purpose of marriage and family is to maintain the human population. Meanwhile, today's modern humans are faced with the threat of overpopulation of mankind. It is in this context that childfree is studied. This study focuses on the views of Islamic law on childfree. This focus is revealed in research questions about the concept and factors of childfree, and its status in view of the purpose of marriage in Islam (maqasid al-nikah). Qualitative methods are used in this study by utilizing library research. The approach used is the philosophy of Islamic law. Data collection is done by documentation. While the analysis is carried out in a cycle-systemic manner. This research concludes; First, Childfree is one of the choices of modern humans in running a family system. Happiness in a family through Childfree is not determined by the presence of offspring. Second, Childfree is inconsistent with the purpose of marriage (maqasid al-nikah) in Islam. This is because it has the potential to threaten the existence of the continuity of human life on earth.